Re-Imagining Approaches to Learning and Teaching: Youth and Community Work Education Post COVID-19 - Sheila Curran; Sinead Gormally; Christine Smith (MDPI AG, 2022)
This article draws on research undertaken by the Professional Association of Lecturers in Youth and Community Work (PALYCW) in collaboration with the Open University, University of Glasgow and the University of Hull. The authors are all part of a community of practice of lecturers teaching in higher education on Community and Youth Work (CYW) degree programmes. These CYW programmes are professionally endorsed by Youth Work and Community Development professional bodies across the UK. They adopt informal methodologies and have a strong focus on preparing students to work as informal educators with young people and communities. The unique contribution of this paper is highlighting the experiences, issues and challenges presented and exploring creative approaches that have been developed by programmes that adopt these approaches to educate professional practitioners. Looking forward in a context of great uncertainty, the research also set out to consider what the future might look like for CYW programmes, located in the neoliberal university. Questions explored included the extent to which the pandemic might lead to longer term changes in learning and teaching methodologies in CYW in higher education (HE) and how CYW programmes should be preparing students for navigating practice in the society that unfolds post COVID-19 as the basis for taking action in communities in response to new formations of social injustice and inequality with conscious intent.